Analisis Kualitas Butir Soal Asesmen Sumatif Mata Pelajaran Bahasa Indonesia di Sekolah - Siti Kasiyani; Siti Isnaniah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
Exam questions are often designed without prior comprehensive analysis of the quality of each item. As a result, many questions fail to optimally measure student abilities. This study aimed to assess the quality of summative assessment items in the Indonesian language subject for eighth-grade students at Batik Special Program Junior High School, Surakarta, in the 2024/2025 academic year. This study employed a quantitative descriptive approach with the aid of Anates version 4 software to analyze validity, reliability, difficulty level, discriminating power, and distractor effectiveness. The subjects were all 25 eighth-grade students. The data analyzed consisted of 30 multiple-choice questions. Based on the analysis results, several conclusions were obtained: 1) as many as 53% of the questions were included in the valid category, 2) the reliability coefficient showed a value of 0.72 which placed the questions in the high reliability category, 3) the difficulty level of most of the questions was at the easy to very easy level, 4) the discriminating power analysis showed that 37% of the questions did not have the ability to differentiate students well, 5) the effectiveness of distractors indicated that most of the answer options did not function optimally. These findings indicate that the quality of the questions still needs to be improved, especially in the aspects of discriminating power and distractor effectiveness, so that it can be used as a basis for improving the preparation of assessment instruments in the future.